Action-angle variables and novel superintegrable systems; Physics of Atomic Nuclei; Vol. 73, iss. 5 - Hakobyan T.; Lechtenfeld O.; Nersessian A. P. Armen Petrosovich; Saghatelian A.; Yeghikyan V. (2012, 2012)
Title screen